2015
DOI: 10.1007/s12035-015-9480-z
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Delivery of RGD Motif-Containing Osteopontin Icosamer Confers Neuroprotection in the Postischemic Brain via αvβ3 Integrin Binding

Abstract: Osteopontin (OPN) is a phosphorylated glycoprotein possessing an arginine-glycine-aspartate (RGD)-motif, which binds to several cell surface integrins and mediates a wide range of cellular processes. Inductions of OPN have been reported in the postischemic brain, and the neuroprotective effects of OPN have been demonstrated in animal models of stroke. In the present study, we showed a robust neuroprotective effect of RGD-containing icosamer OPN peptide (OPNpt20) in a rat model of focal cerebral ischemia (middl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 40 publications
2
38
0
Order By: Relevance
“…18 molecule consisting of only 20 amino acids (RGD-containing icosamer OPN) displays stronger neuroprotective abilities in vivo compared to full-length OPN, and additionally decreases the induction of iNOS and NO-release in primary microglia in vitro (Jin et al , 2015). In line with these studies, we found OPN to reduce the expression of iNOS and the release of NO from rat microglia stimulated with LPS.…”
Section: Accepted Manuscriptsupporting
confidence: 81%
See 1 more Smart Citation
“…18 molecule consisting of only 20 amino acids (RGD-containing icosamer OPN) displays stronger neuroprotective abilities in vivo compared to full-length OPN, and additionally decreases the induction of iNOS and NO-release in primary microglia in vitro (Jin et al , 2015). In line with these studies, we found OPN to reduce the expression of iNOS and the release of NO from rat microglia stimulated with LPS.…”
Section: Accepted Manuscriptsupporting
confidence: 81%
“…A pro-survival effect of OPN has been attributed to the phosphatidylinositol 3-kinase (PI3K)/Akt pathway Yang-Yen, 2001, Topkoru et al , 2013), while OPN has been linked to reduce NO-levels through integrin binding and STAT-ubiquitination (Gao, Guo, 2007, Jin, Lee, 2015.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Fibronectin and vitronectin induce microglial activation via the integrins α5β1 and αvβ5, respectively ( 26 ). Furthermore, Jin et al found that RGD-containing icosamer OPN peptide (OPNpt20) confers anti-inflammatory effect in primary microglia cultures, which was obtained by αvβ3 integrin mediated suppression of iNOS induction, indicating the critical roles of αvβ3 integrin in mediating the physical and functional cell-cell or cell-matrix interactions ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms thought to be associated with OPN-mediated neuroprotection include binding to the cell surface αvβ3 integrin receptor to stimulate pro-survival signaling (i.e., PI3K/Akt pathway), anti-inflammatory effects [126,129,130,131], inhibition of inducible NOS [132,133] STAT1 ubiquitination/degradation and by reducing MMP-9 and NF-κβ activation. Despite OPN’s demonstrated neuroprotective effects, in one study OPN deficient mice demonstrated no change in susceptibility to ischemic brain injury [126].…”
Section: Neuroprotective Peptides and Their Therapeutic Applicatiomentioning
confidence: 99%